Ovarian Teratoma in a Young Bitch - Ludwig, Jane Kelly; da Silva Fonseca, Ruth Ely; Dall'Agnol Krause, Catherine; Pioner de Jesus, Bruna; Froner Argenta, Fernando; Elias Klein, Fábio; Zafalon-Silva, Bruna; Barreto Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2024)
Background: Ovarian teratoma is a neoplasm originating from totipotent cells with residual cellular components of more than one germinative layers and is characterized by lack of tissues except ovarian. It usually presents benign behavior and cystic forms and affects elderly females; though considered rare in young animals. The presumptive and definitive diagnoses are achieved using radiography and ultrasonography imaging and histopathological and immunohistochemistry evaluations, respectively. Surgical excision is the recommended treatment in dogs and cats by therapeutic ovariosalpingohysterectomy. The primary aim is to report ovarian teratoma occurrence in a young female dog with rapid evolution. Case: A female dog, Labrador breed, not spayed, weighing 24.1kg and aged approximately 1 year and 11 months, was prescribed an exploratory laparotomy after consultation with a history of abdominal swelling after heat. A total abdominal ultrasound was previously performed in which a big abdominal mass was observed next to the uterus and ovarian region, and an abdominal radiography examination revealed a mass measuring 19.81 cm x 14.59 cm and presented a radiopaque point in its interior. On physical examination the animal presented abdominal bulging, slight dyspnea and abdominal pain during palpation, and other physiological parameters within normal range. After consultation, an exploratory laparotomy followed by therapeutic ovariosalpingohysterectomy was performed using the modified three-clip technique. The collected material was conditioned in 10% formaldehyde and sent for examination. On macroscopic evaluation, the ovary fragments presented tumoral mass with irregular aspects and skin-like areas, with fur, and soft and hard areas. At the cut, it was dark brown with beige areas, homogeneous and opaque, with multiple irregular dilatations, filled with hair follicles, in addition to areas of bony aspect. For histopathological examination, the tumor fragments were processed with hematoxylin and eosin staining. The organ presented neoplasia proliferation composed of multiple epithelial cell groups arranged in cystic cavities containing keratin, entwined with an intense amount of fibrous conjunctive tissues. Based on these characteristics, the dog was diagnosed with ovarian teratoma. Discussion: The diagnosis was achieved based on the clinical signs and macroscopic examination of histopathological injuries. Abdominal distension was the main clinical sign and tutor’s complaint in a young female dog after heat, which is consistent with that reported in literature. Although age group is not yet well defined, reports often include elderly female dogs, which turns this as a particular case since the patient was < 2 years old. From histopathological analysis it was revealed that the nodule possessed generated multiple follicles and hair shafts along with nervous tissue areas, including neurons, glial cells, and neuropils. Additionally, it possessed multifocal areas of cartilaginous, bone and adipose tissues, corroborating with studies describing teratoma originating from foreign tissues to the ovary and descendent from different germinative layers. Therefore, it is concluded that teratoma in young females rarely occurs, and surgical treatment that is instituted is effective. In general, a presumptive diagnosis is recommended through imaging examinations, and definitive diagnosis through histopathological analysis. Keywords: histopathology, neoplasm, ovariosalpingohysterectomy. Título: Teratoma ovariano em uma cadela jovem Descritores: histopatologia, neoplasia, ovariossalpingo-histerectomia.